2000
DOI: 10.1159/000017429
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Progenitor Cell Responsiveness to Bone Morphogenetic Proteins Differentially Modulate Progressive CNS Lineage Fate

Abstract: Although multipotent progenitor cells capable of generating neurons, astrocytes and oligodendrocytes are present within the germinal zones of the brain throughout embryonic, postnatal and adult life, the different neural cell types are generated within discrete temporospatial developmental windows. This might suggest that multipotent progenitor cells encounter different signals during each developmental stage, thus accounting for separate waves of lineage commitment and cellular differentiation. This study dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(151 citation statements)
references
References 50 publications
6
144
0
1
Order By: Relevance
“…Other studies have found that the effects of BMPs can be age and tissue dependent (Grinspan et al, 2000;Mehler et al, 2000). Although BMP promoted both neuronal and astroglial differentiation when applied to cultures of cortical cells plated at E16, BMP2 induced neuronal cell death at earlier ages (Mabie et al, 1999).…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have found that the effects of BMPs can be age and tissue dependent (Grinspan et al, 2000;Mehler et al, 2000). Although BMP promoted both neuronal and astroglial differentiation when applied to cultures of cortical cells plated at E16, BMP2 induced neuronal cell death at earlier ages (Mabie et al, 1999).…”
Section: Discussionmentioning
confidence: 95%
“…At early stages of neurogenesis, exposing stem cells and progenitor cells in the telencephalic VZ to BMP-2 or BMP-4 increases apoptosis and inhibits proliferation, whereas at later stages BMP-2 or BMP-4 signaling promotes neuronal differentiation by inducing the expression of the neuron-specific class II b-tubulin (Tuj1) through activation of the Erk mitogenactivated protein kinase (MAPK) pathway Mabie et al 1999;Mehler et al 2000;Moon et al 2009). Forebrain explants exposed to BMP-4 downregulate anterior neural gene expression, and deletion of BMP antagonists causes loss of anterior brain structures (Furuta et al 1997;Anderson et al 2002).…”
Section: Forebrainmentioning
confidence: 99%
“…Previous studies have reported that neural progenitor cells of the adult SVZ can be driven to astrocytic phenotype by bone morphogenetic proteins (BMPs), in particular BMP-2 and BMP-4 [130][131][132]. High concentrations of these BMPs and their receptors have been identified in the SVZ of the adult rat brain [130,132] and may dictate the glial bias of newly generated cells in the adult subependyma.…”
Section: Suppression Of Bone Morphogenetic Proteins (Bmps) Can Be Usementioning
confidence: 99%
“…High concentrations of these BMPs and their receptors have been identified in the SVZ of the adult rat brain [130,132] and may dictate the glial bias of newly generated cells in the adult subependyma. Yet at the same time, ventricular ependymal cells can express Noggin, an endogenous antagonist of the BMP family, thereby defining local niches that may remain permissive for neuronal cell fate [133][134][135][136].…”
Section: Suppression Of Bone Morphogenetic Proteins (Bmps) Can Be Usementioning
confidence: 99%